2018
DOI: 10.1016/j.foreco.2018.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Land use legacies on forest understory vegetation and soils in the Mediterranean region: Should we use historical maps or in situ land use remnants?

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 48 publications
(74 reference statements)
0
18
0
Order By: Relevance
“…Furthermore, land‐use legacies often enforce lagging ecosystem dynamics, so that ecosystems with a slower development have more potential to be influenced by their effects (Bürgi et al, ). Effects of land‐use legacies are consequently well‐documented in temperate forests, and on community dynamics in the herbaceous understorey layer in particular (Abadie et al, ; Brudvig, Grman, Habeck, Orrock, & Ledvina, ; Hermy & Verheyen, ; Newbold et al, ; Verheyen, Bossuyt, Hermy, & Tack, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, land‐use legacies often enforce lagging ecosystem dynamics, so that ecosystems with a slower development have more potential to be influenced by their effects (Bürgi et al, ). Effects of land‐use legacies are consequently well‐documented in temperate forests, and on community dynamics in the herbaceous understorey layer in particular (Abadie et al, ; Brudvig, Grman, Habeck, Orrock, & Ledvina, ; Hermy & Verheyen, ; Newbold et al, ; Verheyen, Bossuyt, Hermy, & Tack, ).…”
Section: Introductionmentioning
confidence: 99%
“…The response of other taxa — insects (e.g., Assmann, 1999), lichens (e.g., Janssen et al, 2019), fungi (e.g., Spake et al, 2016) — to forest continuity has also been studied, and despite variations in the magnitude and significance of the effects, have overall highlighted the importance of ancient forests for conservation. However, although some studies have been carried out in areas other than temperate lowland forests, as is the case in mountain and mediterranean areas (Sciama et al, 2009; Abadie et al, 2018; Janssen et al, 2018), several forest types have been largely ignored in historical ecology (Bergès & Dupouey, 2021). This is especially the case for riparian forests, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, thermophilous deciduous, broadleaved evergreen and coniferous forests and woodlands represent a wide range of habitats of conservation concern in the Mediterranean (Gauquelin et al 2018). In this context, human disturbance has, among others, caused simplification of forest structure, changes in plant composition, abundance and distribution (Blasi et al 2010, Abadie et al 2018. Moreover, forest conversions into managed systems have been proven to decrease the capacity of storing carbon below ground due to simplification of foliage and root litter inputs (Błonska et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the Mediterranean Basin, Amici et al (2013) showed that light-demanding species richness decreased with increasing successional age of forest. Plant species in old-growth forests are often specialists, with short distance dispersal mechanisms and no persistent soil seed bank, which makes them more vulnerable to forest habitat loss (Burrascano et al 2009, Campetella et al 2016, Abadie et al 2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation